Service Improvement through Customer Service Training at the Luhur Medika Center Primary Clinic - Angga Dewi Anggraeni; Senny Handayani Suarsa; Asaretkha Adjane Annisawati; Tamadara Hilman (Jurnal Pengabdian Pada Masyarakat, 2023)
Luhur Medika Center (LMC) Primary Clinic is a company engaged in the pharmaceutical and health sector that provides primary and specialist medical health services. As a primary clinic, LMC needs to provide quality essential medical services, be easily accessible and provide services at affordable prices. However, several obstacles are experienced by the clinic, especially regarding services. Among them are consumer complaints regarding the length of waiting time, lack of serving staff, and uninformative customer service. With competent customer service, service can be improved by reducing patient waiting time and patient scheduling, so patients do not need to be crowded in the waiting room. One way is through customer service training. The customer service training program was chosen to train frontline employees with basic knowledge of handling consumers well and increase customer satisfaction. The training methods used in this activity are the preparation and implementation stages, program evaluation, and reporting. The results show that the program has been achieved, marked by an increase in participants' understanding and knowledge so that the results can be applied and utilized by participants and the LMC clinic as a partner of this training program.